2022
DOI: 10.1097/aco.0000000000001117
|View full text |Cite
|
Sign up to set email alerts
|

When is it safe to resume anticoagulation in traumatic brain injury?

Abstract: Purpose of reviewWhen to resume or initiate anticoagulation therapy following traumatic brain injury (TBI) is controversial. This summary describes the latest evidence to guide best practice. Recent findingsFollowing trauma, prophylactic, and therapeutic anticoagulation (TAC) have been widely encouraged to prevent major comorbidities such as pulmonary embolism and deep venous thrombosis. Increased rebleeding risk and potentially catastrophic outcome from initiation of anticoagulation treatment in TBI are mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…A study involving 1,215 patients showed that those treated with Low Molecular Weight Heparin (LMWH) had an 18% higher risk of hemorrhage progression (24% vs. 42%) compared to patients not treated with anticoagulants [22] . The majority of literature suggests that initiating pharmacological prophylaxis for anticoagulation 24-72 hours after hemostasis in TBI is considered safe [18,[23][24][25][26] . A prospective analysis indicated that TBI patients treated with Unfractionated Heparin (UFH) after 24 hours of injury stability on CT had a bleeding progression rate of 0.78%, compared to 2.8% in patients without pharmacological prophylaxis, with no statistically signi cant difference (P = 0.33) [18,24] .…”
Section: Tbi and Prophylactic Anticoagulation Therapymentioning
confidence: 99%
“…A study involving 1,215 patients showed that those treated with Low Molecular Weight Heparin (LMWH) had an 18% higher risk of hemorrhage progression (24% vs. 42%) compared to patients not treated with anticoagulants [22] . The majority of literature suggests that initiating pharmacological prophylaxis for anticoagulation 24-72 hours after hemostasis in TBI is considered safe [18,[23][24][25][26] . A prospective analysis indicated that TBI patients treated with Unfractionated Heparin (UFH) after 24 hours of injury stability on CT had a bleeding progression rate of 0.78%, compared to 2.8% in patients without pharmacological prophylaxis, with no statistically signi cant difference (P = 0.33) [18,24] .…”
Section: Tbi and Prophylactic Anticoagulation Therapymentioning
confidence: 99%
“…раздел «Обсуждение») может привести к значимому увеличению объема исходной гематомы при рецидиве кровоизлияния. В то же время задержка медикаментозной профилактики или отказ от нее сопровождаются высоким риском ВТЭО, включая фатальные ТЭЛА [3,[12][13][14].…”
Section: ' 2024unclassified
“…введение Нейрохирургические и неврологические пациенты остаются категорией больных с высоким или крайне высоким риском венозных тромбоэмболических осложнений (ВТЭО), которые включают тромбоз вен нижних конечностей и тромбоэмболию легочной артерии (ТЭЛА) [1][2][3][4]. Особенно это касается заболеваний, при которых имеют место первичные и вторичные внутричерепные кровоизлияния: геморрагический инсульт, кровоизлияния в опухоли головного и спинного мозга, ишемический инсульт с геморрагическим пропитыванием [5][6][7].…”
unclassified
“…Ischemic cerebrovascular disease, cardiovascular disease, and thromboembolic events are common causes for taking antithrombotic agents. 24 26 29) When TBI occurs in patients with these diseases, there is a conflict between the diseases, which require an antithrombotic effect, and the neurosurgeon, who has to minimize intracranial hemorrhage. Nevertheless, there are no clear guidelines for the reversal or resumption of antithrombotic agents when TBI occurs in patients taking antithrombotic agents.…”
Section: Introductionmentioning
confidence: 99%